Effects of pipes corrugated shapes on the friction factor (2012)
Corrugated pipes are pipes with walls of rough surfaces consisting of discrete grooves periodically disposed along the flow direction and commonly use in engineering application such as irrigation, delivery devices to main distribution ducts as in transport of Liquid Natural Gas from ships to the mainland distribution network and heat exchanger in heating, ventilation, air-conditioning etc. The simulation of turbulent, incompressible, isothermal and single-phase flow is considered for five geometric configurations of corrugated surfaces with the different groove heights, length and spacing were evaluated in order to compare their influence on the friction factor. The numerical analysis was carried out using computational fluid dynamics, and the two-equation turbulence models was used to compute the friction factors and Reynolds number for comparison. The results shows that the friction factor is not solely depend on the roughness height but also on the thickness ofthe roughness and space between successive roughness.